2007
DOI: 10.1080/09541440701326063
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive-science based programme to enhance study efficacy in a high and low risk setting

Abstract: In three experiments, learning performance in a 6-or 7-week cognitive-science based computer-study programme was compared to equal time spent self-studying on paper. The first two experiments were conducted with grade 6 and 7 children in a high risk educational setting, the third with Columbia University undergraduates. The principles the programme implemented included (1) deep, meaningful, elaborative, multimodal processing, (2) transfer-appropriate processing, (3) selfgeneration and multiple testing of respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 73 publications
1
42
0
1
Order By: Relevance
“…As in the studies conducted on distributed practice, most experiments on retrieval practice have been conducted using word lists or word pairs (e.g., Bouwmeester & Verkoeijen, 2011;Carpenter, Pashler, & Vul, 2006;Carpenter, Pashler, Wixted, & Vul, 2008;Toppino & Cohen, 2009;Tulving, 1967;Wheeler, Ewers, & Buonanno, 2003) and foreign vocabulary pairs (e.g., Carpenter et al, 2008;Carrier & Pashler, 1992;Fritz, Morris, Acton, Voelkel, & Etkind, 2007;Karpicke, 2009;Karpicke & Roediger, 2008;Pashler, Cepeda, Wixted, & Rohrer, 2005;Pyc & Rawson, 2007Toppino & Cohen, 2009). Some studies have found a beneficial effect of retrieval practice for first language vocabulary learning, with adults (e.g., Cull, 2000;Karpicke & Smith, 2012), as well as with primary school children (e.g., Goossens, Camp, Verkoeijen, Tabbers, & Zwaan, 2014;Metcalfe, Kornell, & Son, 2007). However, none of these studies has been performed in the classroom using materials from the actual vocabulary curriculum.…”
mentioning
confidence: 99%
“…As in the studies conducted on distributed practice, most experiments on retrieval practice have been conducted using word lists or word pairs (e.g., Bouwmeester & Verkoeijen, 2011;Carpenter, Pashler, & Vul, 2006;Carpenter, Pashler, Wixted, & Vul, 2008;Toppino & Cohen, 2009;Tulving, 1967;Wheeler, Ewers, & Buonanno, 2003) and foreign vocabulary pairs (e.g., Carpenter et al, 2008;Carrier & Pashler, 1992;Fritz, Morris, Acton, Voelkel, & Etkind, 2007;Karpicke, 2009;Karpicke & Roediger, 2008;Pashler, Cepeda, Wixted, & Rohrer, 2005;Pyc & Rawson, 2007Toppino & Cohen, 2009). Some studies have found a beneficial effect of retrieval practice for first language vocabulary learning, with adults (e.g., Cull, 2000;Karpicke & Smith, 2012), as well as with primary school children (e.g., Goossens, Camp, Verkoeijen, Tabbers, & Zwaan, 2014;Metcalfe, Kornell, & Son, 2007). However, none of these studies has been performed in the classroom using materials from the actual vocabulary curriculum.…”
mentioning
confidence: 99%
“…In this article, we will investigate one strategy that holds considerable promise for classroom application, namely learning. One study demonstrated that -compared to self-studylearning of definition-word pairs in sixth and seventh grade children was enhanced by using a computer program in which retrieval practice was included (Metcalfe, Kornell, & Son, 2007). In another study third graders practiced twenty words and their synonyms (Goossens, Camp, Verkoeijen, & Tabbers, 2014).…”
mentioning
confidence: 99%
“…If learners, for example, are required to generate information during study (say, generating words from subsets of their letters), they tend to perform better on a later recall test for such information than do learners who simply read that same information presented intact during study. This memorial advantage for generation over reading-referred to as the generation effect (Jacoby, 1978;Slamecka & Graf, 1978; for a review, see Bertsch, Pesta, Wiscott, & McDaniel, 2007)-has been demonstrated to be a robust phenomenon, occurring for a variety of materials and in educational contexts (e.g., deWinstanley, 1995;McNamara & Healy, 1995a, b;Metcalfe, Kornell, & Son, 2007;Pesta, Sanders, & Murphy, 1999).…”
mentioning
confidence: 99%